Governance and the right to health in north-western Syria - Abenza, Omar Ahmed (Journal of the Spanish Institute for Strategic Studies, 2020)
This article highlights i) the lack of respect for the right to health that is being experienced during the Syrian conflict, and ii) the impact of its political significance on the medical humanitarian response, whose mission is precisely that of assisting the people in health matters and thus guaranteeing the minimum standards required by the right to health. We will focus on two issues: 1) non-fulfilment of the right to health in the Syrian conflict, and 2) clarifying the capacity of the existing medical humanitarian response system to uphold the right to health. The confirmed hypotheses are: first, that the right to health is suffering from a serious lack of respect due to the highly politicised nature of the conflict; and second, that the political influence placed on the system of governance of the health response prevents it from lessening the level of non-compliance with the right to health.